Polarization of Global Leadership: An Analysis of the Three Factions of Leadership Power in Modern Leadership Theory - Syafrizal Syafrizal (Budapest International Research and Critics University, 2021)
The purpose of this article is to explain various global developments, especially those related to leadership polarization issues in the superpower countries. Global leadership is not only seen from the perspective of which country and who is elected as its leader, but what is more essential is the extent to which the leadership holds resources in general to be used as an instrument to carry out the hegemony of power. The phenomenon of polarization global leadership: an analysis of the three factions of the leadership strength in leadership theory modern, empirically categorized as one of the important issues because it relates to the harmony of living together with all human beings on this planet. Leadership based on egoism wrapped in style and authoriterm type will certainly bring havoc to mankind. This article was compiled from a research process on various literatures, the process of collecting literature up to the preparation of this article was approximately three months, namely from August to October 2020. Theoretically, several main points and the findings of this article were obtained, that leadership polarization Globally is actually in the control of three factions, including (1) rational superiority leadership power faction, (2) intellectual superiority leadership power faction, (3) physical and spiritual superiority leadership power faction, with three models, namely: (a) Western-style leadership, (b) Eastern-style leadership, and (c) Islamic leadership. However, in the form of the factions and leadership styles above, it is closely related to the ability of a country to play its role in controlling economic, political and social resources. To obtain such advantages, in practice it is not uncommon for a country to first require to build a superiority in the field of defense and security with state-of-the-art weapons.